Persian Translation Study On Arabic Story Of The Collared Dove In Kalila and Dimna/ دراسة الفکر السائد علی قصة الحمامة المطوقة في کلیلة ودمنة وترجمتها الفارسية - Nia, Mahdi Moqadasi; Al Quraishi, Nawras Hashem Jabr Harbi; Firoozjai, Hossein Taktabar (Ijaz Arabi Journal of Arabic Learning, 2024)
Kalila and Dimna, a renowned international literary heritage, has been embraced by various cultures, as evident in its numerous translations worldwide. In this comparative study, we delve into the Arabic text of The ring-necked dove story and its Persian translation, aiming to uncover the cultural nuances and additions introduced by Nasrallah Munshi. Our research, guided by Mona Baker's Framing theory, is based on the version by Abd al-Wahhab Azzam and Taha Hussein for the Arabic text and Mojtaba Minavi's version from the University of Tehran Publisher for the Persian text. The story under scrutiny involves a flock of pigeons trapped, but they escape through cooperation and the aid of a rat. Our descriptive-analytical approach compares the Arabic and Persian texts, revealing the translator's additions and potential justifications. The results highlight a shift in responsibility from the ring-necked dove to the flock of pigeons, a significant finding in this story's cultural adaptation. On the other hand, between the lines of the Arabic text, there is an emphasis on the necessity of cooperation to eliminate disasters. However, in the Persian text, we find an insistence on values such as sacrifice and altruism, as well as the role that lack of attention to the leader's orders plays in the occurrence of disasters and misfortunes, as well as the effect of the wisdom that the leader possesses in That's it, people. In other words, the translator is trying to exaggerate the role of the leader in saving his nation. At the same time, Ibn Muqaffa focuses on cooperation's role in achieving this salvation. This study helps researchers know the differences in Arabic stories and their translation into various international languages while introducing the Arab literary heritage to students.